2019
DOI: 10.1017/jfm.2019.621
|View full text |Cite
|
Sign up to set email alerts
|

Numerical stability analysis of a vortex ring with swirl

Abstract: The linear instability of a vortex ring with swirl with Gaussian distributions of azimuthal vorticity and velocity in its core is studied by direct numerical simulation. The numerical study is carried out in two steps: first, an axisymmetric simulation of the Navier–Stokes equations is performed to obtain the quasi-steady state that forms a base flow; then, the equations are linearized around this base flow and integrated for a sufficiently long time to obtain the characteristics of the most unstable mode. It … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 39 publications
3
20
0
Order By: Relevance
“…Note that these are typical eigenfunctions for vortex rings subjected to elliptic instability, which are also reported elsewhere (Gargan-Shingles et al 2016; Hattori et al 2019). A couple of eigenfunctions of the rotating modes that look qualitatively similar to the spiral modes of Hattori et al (2019) are shown in figure 8. We could track these modes only for the viscous Gaussian cases (see table 4), while neither for the corresponding inviscid cases nor for any of the equilibrated cases were these found.…”
Section: Global Stability Resultssupporting
confidence: 81%
See 2 more Smart Citations
“…Note that these are typical eigenfunctions for vortex rings subjected to elliptic instability, which are also reported elsewhere (Gargan-Shingles et al 2016; Hattori et al 2019). A couple of eigenfunctions of the rotating modes that look qualitatively similar to the spiral modes of Hattori et al (2019) are shown in figure 8. We could track these modes only for the viscous Gaussian cases (see table 4), while neither for the corresponding inviscid cases nor for any of the equilibrated cases were these found.…”
Section: Global Stability Resultssupporting
confidence: 81%
“…Vortex rings are themselves unstable to azimuthal perturbations, whose inviscid asymptotic theories were developed in Widnall & Sullivan (1973) and Widnall, Bliss & Tsai (1974), for slender rings whose core radius , the ring radius. These were later extended to viscous flows (Eloy & Le Dizés 2001; Fukumoto & Hattori 2005), while viscous growth rates have also been extracted from direct numerical simulations (DNS) (Shariff, Verzicco & Orlandi 1994; Archer, Thomas & Coleman 2008; Hattori, Blanco-Rodríguez & Le Dizés 2019). In this work a detailed global, modal stability analysis of vortex rings for both inviscid and viscous flows is performed where one of the primary aims is to clarify some of the existing discrepancies between asymptotic theories and numerical simulations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The effect of an axial flow in the vortex cores was analysed by Fukumoto & Miyazaki (1991). More recently, global temporal stability characteristics were also derived by Okulov (2004) and Okulov & Sørensen (2007) using Hardin's expressions. In all these works, the core size is assumed small and short-wavelength instabilities (Blanco-Rodríguez & Le Dizès 2016Hattori, Blanco-Rodríguez & Le Dizès 2019) that may develop in vortex cores are neglected.…”
Section: Introductionmentioning
confidence: 99%
“…Such a procedure has also been employed in previous studies e.g. [42][43][44][45]. It should be noted that since no stabilization or restriction (aside from streamwise periodicity) is imposed on the flow, the baseflow may contain a low amplitude component of possibly unstable eigenmodes at the end of the adaptation stage.…”
Section: Stability Analysismentioning
confidence: 99%